2021
DOI: 10.1007/s00417-021-05214-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in the aqueous humor of patients with different types of glaucoma

Abstract: Purpose The aim of the study was to compare the frequency and the level of expression of selected miRNAs in the aqueous humor of patients with various types of glaucoma. Methods The studied group consisted of 42 patients with glaucoma: 19 with primary open-angle glaucoma (POAG), 14 with pseudoexfoliation glaucoma (PEXG), 9 with primary angle closure glaucoma (PACG), and the control group of 36 patients with senile cataract without glaucoma. The real-time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…miRNAs are tissue-specific and expressed in ocular tissues related to glaucoma [ 35 ]. Several studies have highlighted the significant role of miRNAs and their plausible underlying mechanisms in different types of glaucoma, including PXG [ 8 , 36 , 37 , 38 , 39 , 40 ]. Rao et al reported the overexpression of 12 miRNAs in PXG, of which miR-122-5p, miR-124-3p, and miR-424-5p targeted TGFβ1, fibrosis/ECM, and proteoglycan metabolism pathways [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs are tissue-specific and expressed in ocular tissues related to glaucoma [ 35 ]. Several studies have highlighted the significant role of miRNAs and their plausible underlying mechanisms in different types of glaucoma, including PXG [ 8 , 36 , 37 , 38 , 39 , 40 ]. Rao et al reported the overexpression of 12 miRNAs in PXG, of which miR-122-5p, miR-124-3p, and miR-424-5p targeted TGFβ1, fibrosis/ECM, and proteoglycan metabolism pathways [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have reported the miR-29 family as an essential modulator of ECM genes under chronic oxidative stress conditions and TGFß stimulation in the human TM cells [ 44 , 45 ]. miR-1260b, mainly involved in the process of hypoxia and apoptosis, was reported to be most abundantly expressed in PXG [ 38 ]. Hindle et al reported 20 circulatory miRNAs targeting neuroinflammation, nitric oxide, and neurotrophin–tropomyosin-related kinase (TRK) signaling pathways [ 40 ], which have all been strongly implicated in the pathophysiology of glaucoma [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathway analysis revealed that these miRNAs are involved in potential glaucoma pathways including tight junctions and TGF-β signaling, all of which are known in XFS pathogenesis. Another study, however, found no difference in miRNA expression between the different kinds of primary glaucoma, though hsa-miR-6722-3p, hsa-miR-184, and hsa-miR-1260b were more frequently found in XFG and POAG, respectively [42]. Another study identified higher levels of expression of 20 miRNAs in XFG and POAG patients than in controls, with 6 out of the 20 miRNAs (miR-637, miR-99b-3p, miR-4725-3p, miR-4724-5p, miR-4358, and miR-433-3p) elevated in both plasma and AH [43].…”
Section: Potential Role Of Mirnas In Xfgmentioning
confidence: 92%
“…In recent times, anterior chamber paracentesis to obtain aqueous humor (AH) is becoming a study technique of great interest due to the information it provides. In the same way that allows the analysis of miRNAs in non-oncologic ophthalmologic diseases ( Grieco et al, 2020 ; Zhu et al, 2020 ; Kosior-Jarecka et al, 2021 ), it is also considered a great alternative in tumor biopsy for RB ( Gudiseva et al, 2019 ). Numerous publications have studied in AH the presence of RB biomarkers such as Lactate Dehydrogenase (LDH), Neuron-Specific Enolase (NSE) and Survivin among others ( Ghiam et al, 2019 ).…”
Section: Mirnas In Rbmentioning
confidence: 99%